A computational model for aneurysm growth - Khairul Faezi, Mohamad Alias@Ayit (2010)
The aneurysm is the abnormal bulging of a portion of an artery due weakness in the cerebral. This occurs when the mechanical behaviour exceeds the strength of the tissue. Investigation on the changes of flow phenomena and the mechanical behaviour in cerebral aneurysm had been studied. This thesis was focus on the computational model for cerebral aneurysm growth. The main objectives of this project are to investigate the important role of wall shear stress in initiation, growth and rupture of aneurysm and also the wall deformation due to the blood flow. The simulation had been done by using different geometry of aneurysms and analyzed in the MSC Patran and MSC Dytran software. In this analysis, the size of geometry diameter and thickness were varied in order to analyze the Fluid Structure Interaction between the arterial structure and the blood flow. The geometry thickness that had been used in this analysis was 0.35 mm, 0.45 mm and 0.55 mm. After the analysis, the maximum displacement of the cerebral aneurysm wall was increased and wall shear stress was decreased by the increasing of diameter of the cerebral. The maximum displacements for different thickness are 0.005111 mm, 0.005094 mm and 0.005078 mm. The maximum wall shear stresses for different thickness are 0.9167 Pa, 1.1078 Pa and 1.1683 Pa. As the size of an aneurysm increases, there is a potential of rupture of aneurysm and this can result in severe hemorrhage or even worst, fatal event. To avoid an aneurysm rupture, research must be carry out to find the alternative to solve this problem which is more valuable to people that have been suffered because of aneurysms.